Polyunsaturated fatty acids from microalgae Spirulina platensis modulates lipid metabolism disorders and gut microbiota in high-fat diet rats. (September 2019) - Li, Tian-Tian; Tong, Ai-Jun; Liu, Yuan-Yuan; Huang, Zi-Rui; Wan, Xu-Zhi; Pan, Yu-Yang; Jia, Rui-Bo; Liu, Bin; Chen, Xin-Hua; Zhao, Chao
Abstract: Effects of Spirulina platensis 55% ethanol extract (SPL55) on lipid metabolism in high-fat diet-induced hyperlipidaemic rats were investigated. Ultra performance liquid chromatography-quadrupole time-of-flight mass spectrometry indicated that SPL55 was enriched with polyunsaturated fatty acids. Meanwhile, serum and liver lipid levels, including total triglyceride, total cholesterol, and low-density-lipoprotein cholesterol, were significantly decreased in hyperlipidaemic rats of SPL55. Analysis of tissue sections showed that SPL55 treatment could markedly inhibit hepatic lipid accumulation and steatosis. Moreover, SPL55 regulated the mRNA and protein expression levels of SREBP-1c, HMG-CoA, PEPCK, ACC, and AMPK genes involved in lipid metabolism. Furthermore, SPL55 led to decrease the abundances of Turicibacter, Clostridium_XlVa, and Romboutsia, which were positive correlation with lipid metabolism indicators, and has also enriched Alloprevotella, Prevotella, Porphyromonadaceae, and Barnesiella . These results provided evidence that SPL55 might be developed as a functional food to ameliorate lipid metabolic disorders and hyperlipidaemia. Graphical abstract: Image 1 Highlights: SPL55 was enriched with polyunsaturated fatty acids including linoleic acids and γ-linolenic acid. SPL55 has the potential to improve serum and hepatic lipid metabolic disorders in rats with hyperlipidemia. SPL55 administration attenuated diet-induced hepatic steatosis and modified gut microbiota composition. mRNA and protein expressions levels involved in lipid and glucose metabolism were regulated by SPL55. SPL55 ameliorate lipid metabolism disorder in part through specific genera of gut microbiota.